VERIFYING OF BETA CONVERGENCE FOR SOUTH EAST COUNTRIES OF ASIA - Yusran, Husna Leila; BlaÅ¡ko, Michaela (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2017)
The convergence means the process of balancing disparities in chosen indicators of homogeneous economic groups. Î²-convergence and is based on the assumption, where less developed economy grows faster than advanced ones, so GDP per capita has higher speed in less developed economy. In this article is verified Î² convergence based on dependency between the growth of real GDP per capita and the initial level of real GDP per capita (in PPP) and by modifications of this relationship by using of Least Squares Method for 9 countries of South East Asia in different samples since 2000 till 2015. For completely explanation of dependency and calculation of consistent, minimal estimator are used dummies and created a structural parameter, which eliminate shocks and possible disparities between chosen countries. Based on reached results was proved convergence just in sample since 2004 till 2008 between chosen nine countries of South East Countries of Asia.